Peran Pendidik Dalam Pembentukan Karakter Anak Usia Dini Di Taman Posyandu Sekartaji Desa Ketawang Kecamatan Purwoasri Kabupaten Kediri - Nurul Fitria Aprilia; Ummidlatus Salamah (Alzam: Journal of Islamic Early Childhood Education, 2023)
Early Childhood Education (ECD) is one of the aimed at the development of children from birth up to the age of six years, which is done through the provision of educational stimulation to help the growth and development of children physically and mentally in order to have the readiness to enter further education. The problem of this research is How teacher in Role Character Formation of Early Childhood at Taman Posyandu Sekartaji in Sub Ketawang Purwoasri District of Kediri city. The research objective was to determine the role of Educator in Early Childhood character formation in Taman Posyandu Sekartaji in Sub Ketawang Purwoasri District of Kota Kediri. This research uses descriptive qualitative research. Determination of research areas using snowball sampling technique. The findings indicate that, in the character formation of children is necessary because it can change their development to be good, such as self-discipline, and responsibility, honest, self-confident and have good morals. The conclusion of the researchers is that the role of educators in shaping the character of early childhood is very necessary to be done early, will awaken independence in children and discipline. Advice can be given by researchers to educators, educators should have a good role to make children who have good character and educators should also have the ability to create engaging learning activities so that the children would go to school with full of spirit.